2015
DOI: 10.1080/1540496x.2015.1047300
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Risk-Taking Channel of Monetary Policy in Turkey

Abstract: The mechanism by which monetary policy affects financial institutions' risk perception and/or tolerance has been called the 'risk-taking channel' of monetary policy. It has been recently argued that periods of low interest rates due to expansionary monetary policy, might induce an increase in bank risk-appetite and risk-taking behavior. This paper investigates the bank specific characteristics of risk-taking behavior of the Turkish banking sector as well as the existence of risk taking channel of monetary poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 83 publications
1
16
1
4
Order By: Relevance
“…That crisis proved that even the most advanced financial systems are vulnerable to uncertainties, which can lead to failures both for the domestic financial system and international financial markets and could have detrimental consequences on the real economy. The crisis was sparked by excessive credit expansion and the burst of a chain of bubbles in the real estate market (Özşuca & Akbostanci, 2016). These events led to instability in the global credit market which led to a realisation of an existing threat to the stability of the global financial market.…”
Section: Introductionmentioning
confidence: 99%
“…That crisis proved that even the most advanced financial systems are vulnerable to uncertainties, which can lead to failures both for the domestic financial system and international financial markets and could have detrimental consequences on the real economy. The crisis was sparked by excessive credit expansion and the burst of a chain of bubbles in the real estate market (Özşuca & Akbostanci, 2016). These events led to instability in the global credit market which led to a realisation of an existing threat to the stability of the global financial market.…”
Section: Introductionmentioning
confidence: 99%
“…However, Özşuca and Akbostancı found that large, liquid and well-capitalized banks are less prone to risk-taking. 19…”
Section: Introductionmentioning
confidence: 99%
“…When scholars focus on a wider range of areas, based on a sample of 181 large banks in 15 European countries, it more strongly supports the positive correlation point of view. This situation also exists in China through the data tracking of more than 70 commercial banks in China from 2003 to 2010, found that this positive correlation is also applicable in the Chinese banking industry [16].…”
Section: Macro-prudential Policy and Risk-taking Of Commercial Banksmentioning
confidence: 81%